Strategies to revitalize urban markets as active public space that foster social interaction - Yen, Pung Juo; Mohamad Jamil, Mohd Azli; A. M. R., Aminuddin; Mohmad Shukri, Sharyzee; Md Noor, Md Pilus (Pertubuhan Arkitek Malaysia, 2022)
Urban markets located in the city act as a nodal point which is able to gather people from different demographics to sell and buy. It also provides a platform for social interaction for the surrounding neighbourhood. Thus, the market is a place where a sense of community can be developed. However, the role of the urban market to serve as an unofficial social hub has lost due to the rapid modernisation and the rise of modern retails. The previous studies only focused on the factors that caused the issues and still lacked the architectural criteria to create social spaces to enhance social function of the urban market. Hence, this study is to identify the strategies to revitalize the urban market in order to stimulate social aspects in the city. In this research, case study on the existing urban market will be used as the research inquiry and interview will be conducted with the users of the marketplace. This research will explore the design criteria to revitalize urban markets to foster social interaction across different groups of people. This research will contribute to the enhancement of the sense of community and stimulate the social aspect in urban areas by revitalizing the urban marketplace. It will benefit the local community or urban dweller to ensure their social well-being. Future research can add more variables to the existing study, for instance, the political and economic aspects that influence the social role of the urban markets.